Characterization of bioactive and fruit quality compounds of promising mango genotypes grown in Himalayan plain region - Neetu Saroj; K. Prasad; Sanjay Kumar Singh; Vishal Kumar; Shubham Maurya; Poonam Maurya; Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar (PeerJ, 2023)
Twenty mango genotypes grown in the plains of the Himalayas were characterized by their physical, physiological, biochemical, mineral and organoleptic attributes: fruit firmness, weight, peel thickness, shape, dry seed weight, respiration rate, weight loss, and shelf life. Biochemical attributes such as soluble solids, total carotenoids, total phenolic content, antioxidant activity, titratable acidity, ascorbic acid and total sugars were also determined. In addition, mineral content and fruit-softening enzymes were measured, and an organoleptic evaluation was performed. Polygalactouronase (PG), pectin methylesterase (PME) and lipoxygenase (LOX) were measured from the pulp adjacent to the peel. Similarly, biochemical attributes and mineral content were evaluated using fruit pulp, while organoleptic evaluation included fruit pulp characters and the fruit’s external appearance. The results of the study showed that the ‘Malda’ genotype exhibited the highest total phenolic content (560.60 µg/100 g), total antioxidant (5.79 µmol TE/g), and titratable acidity (0.37%) among the tested genotypes. ‘Amrapali’ had the highest soluble solid content (25.20 °B), ‘Jawahar’ had the highest ascorbic acid content (44.20 mg/100 g pulp), ‘Mallika’ had the highest total flavonoid content (700.00 µg/g) and ‘Amrapali’ had the highest total carotenoid content (9.10 mg/100 g). Moreover, the genotypes ‘Malda’, ‘Safed Malda’and ‘Suvarnarekha’ had a shelf life of 4–5 days longer than other tested genotypes. The genotypes with high biochemical attributes have practical utility for researchers for quality improvement programmes and processing industries as functional ingredients in industrial products. This study provides valuable information on the nutritional and functional properties of different mango genotypes, which can aid in developing improved varieties with enhanced health benefits and greater practical utility for processing industries.